PELATIHAN PERHITUNGAN ANALISIS STANDAR SATUAN BELANJA PADA ORGANISASI PERANGKAT DAERAH DI KABUPATEN BOMBANA - Husin; Nurwati; Rostin; Asriani Achmad (Bajang Institute, 2022)
Purpose and objective of holding the Expenditure Unit Standard Analysis (ASSB) activity as the basis for measuring financial performance in the preparation of the APBD with a performance approach and to analyze the fairness of the workload or costs of each program or activity to be carried out by the Bombana Regency OPD in the preparation of work plans and budgets for OPD in Bombana Regency. Seven models of Standard Analysis of Expenditure Units (ASSB in Bombana Regency, namely Training/Technical Guidance for Employees and Non-Employees, Face-to-Face Socialization/Dissemination, Provision of Daily Food and Drinks for Employees, Provision of Office Stationery, Routine/Periodic Maintenance of Office Buildings, Routine/Regular Maintenance Office Service Vehicles and Routine / Periodic Maintenance of Operational Service Vehicles.